Personality traits and Chinese college students’ satisfaction with physical education classes: the mediating role of trait fluency and the moderating role of physical education class difficulty - Chen, Zhiduo; Tian, Yuge; Li, Min; Yang, Shangjian (Frontiers in Psychology, 2023)
Background: This study aims to investigate the impact mechanism of personality traits on physical education satisfaction among college students, validating the mediating effect of trait flow and the moderating effect of physical education difficulty. By analyzing the influence mechanism of personality traits on college students' satisfaction with physical education classes, it helps to explore more channels to enhance satisfaction with physical education classes. Methods: A questionnaire survey was conducted using the Big Five Personality Scale, the Physical Education Class Satisfaction Scale, the Trait Fluency Scale, and the Physical Education Class Difficulty Scale with 868 public physical education students in 10 universities in Shanghai. Moderated mediation modeling was conducted using Hayes' PROCESS macro. Results: Personality traits are positively correlated with physical education satisfaction, and the predictive effect is significant (β = 0.786, p < 0.001). This association is mediated by trait fluency (indirect effect: β = 0.797, p < 0.001), accounting for 62.7% of the total effect. Physical education difficulty significantly moderates the predictive effects of personality traits on physical education satisfaction (β = -0.183, p < 0.01) and trait fluency (β = -0.130, p < 0.001). Additionally, physical education difficulty significantly moderates the predictive effect of trait fluency on physical education satisfaction (β = 0.172, p < 0.001). Conclusion: Personality traits predict physical education satisfaction, with trait fluency playing a mediating role, and physical education difficulty moderates the direct and indirect paths through which personality traits influence physical education satisfaction.